An Iron and Copper System Catalyzed C–H Arylation of Azoles with Arylboronic Acids - Hu, Wei-Ye; Wang, Pei-Pei; Zhang, Song-Lin (Synthesis, 2015)
An efficient, environmentally friendly, and economical new method for arylation reactions of azoles with arylboronic acids via copper–iron-catalyzed C–H and C–B bond activation has been developed. The protocol tolerates a series of functional groups, such as methoxy, nitro, cyano, chloro, and trifluoromethyl groups.
Keywords: environmentally friendly; copper and iron; C–H activation; azoles; arylboronic acids